#Mapping a movement: social media, feminist hashtags, and movement building in the digital age. Issue 2 (2nd April 2020) - Storer, Heather L.; Rodriguez, Maria
ABSTRACT: Online feminist-based hashtag(#) campaigns, such as #WhyIStayed and #MaybeHeDoesntHitYou, have coalesced into the current #MeToo movement: a global movement to end gender-based violence, on and offline. This study examines issue framing domains within the #WhyIStayed campaign, illustrating how social media campaigns serve as a central component in social movement building. Results indicate #WhyIStayed participants contested dominant representations of intimate partner abuse (IPA) in multiple ways, including demonstrating the ubiquity of IPV and challenging victim-blaming. We argue these subversive acts lay the foundation for the contemporary #MeToo movement. Implications for social work and digital social movement scholarship will be discussed.